Brain Network Modularity Predicts Improvements in Cognitive and Scholastic Performance in Children Involved in a Physical Activity Intervention - Chaddock-Heyman, Laura; Weng, Timothy B.; Kienzler, Caitlin; Weisshappel, Robert; Drollette, Eric S.; Raine, Lauren B.; Westfall, Daniel R.; Kao, Shih-Chun; Baniqued, Pauline; Castelli, Darla M.; Hillman, Charles H.; Kramer, Arthur F. (Frontiers in Human Neuroscience, 2020)
Introduction: Brain network modularity is a principle that quantifies the degree to which functional brain networks are divided into subnetworks. Higher modularity reflects a greater number of within-module connections and fewer connections between modules, and a highly modular brain is often interpreted as a brain which contains highly specialized brain networks with less integration between networks. Recent work in younger and older adults has demonstrated that individual differences in brain network modularity at baseline can predict improvements in performance after cognitive and physical interventions. The use of brain network modularity as a predictor of training outcomes has not yet been examined in children. Method: In the present study, we examined the relationship between baseline brain network modularity and changes (post-intervention performance minus pre-intervention performance) in cognitive and academic performance in 8- to 9-year-old children who participated in an after-school physical activity intervention for 9 months (N=78) as well as in children in a wait-list control group (N=72). Results: In children involved in the after-school physical activity intervention, higher modularity of‎ brain networks at baseline predicted greater improvements in cognitive performance for tasks of executive function, cognitive efficiency, and mathematics achievement. There were no associations between baseline brain network modularity and performance changes in the wait-list control group. Discussion: Our study has implications for biomarkers of cognitive plasticity in children. Understanding predictors of cognitive performance and academic progress during child development may facilitate the effectiveness of interventions aimed to improve cognitive and brain health.‎